An Analysis Of Implementation Learning Media Based On Local Wisdom Involves Using Materials And Resources Rooted In The Cultural Knowledge And Traditions At SMA Negeri Plus Satu Atap Wasur Merauke - Nasrawati Nasrawati; Mega Septhiani Angkasawaty (Journal of Innovative and Creativity, 2025)
This research aimed to analyze how local wisdom involves using materials and resources rooted in the cultural knowledge and traditions can be implemented as the learning media. English Teachers of SMA egeri Plus Satu Atap Wasur were the subject of this research, which was consisted of 3 teachers. This research was conducted from November to December 2024. This research used a descriptive approach based on the qualitative method. The data analysis technique were collected through observation and interviews. Research result shows that of the 5 existing aspects only 4 aspects could be implemented in teacher’s teaching media and 1 aspect that could not be implemented. 4 aspect that can be implemented in teacher learning media is; Identity as the Basis for Nationality, Respecting Local Wisdom as a Type of Intellectual Freedom, Learning Relevant to Local Realities, Creating Responsible Citizens. One of the aspects that cannot be implemented is Honoring Variety in Harmony. This cannot be incorporated into the learning media because there is no special initiative from the school, limited facilities, and lack of direct relationship with traditional leaders. Therefore, further support is needed to realize these programs to preserve local culture and instill the value of togetherness to students. Formerly teacher implemented the local wisdom use folklore, food, dance and local people's livelihoods into their learning media.